Designing geometrical learning activities assisted with ICT media for supporting students’ higher order thinking skills - Meryansumayeka; Zulkardi; Putri, Ratu Ilma Indra; Hiltrimartin, Cecil (Journal on Mathematics Education, 2022)
Students' mastery of geometry topics affects their ability to understand other mathematical topics. In addition, students are required to have higher-order thinking skills. Previous research shows that ICT media played an important role in improving students’ higher-order thinking skills. This study was carried out to produce a cuboid volume learning trajectory in ICT-assisted learning that can support students' higher-order thinking skills. This research employed validation design which consisted of three main stages, namely preliminary, experiment, and retrospective analysis. It was held during two main cycles. Sixty-four students of the eighth-grade in Palembang, Ogan Ilir, Manado, and West Papua were involved as research subjects. Data were collected through validation sheets, observations, interviews, and documents in the form of student worksheets. Then, the data were analyzed qualitatively and described narratively. The learning design developed was able to help students use higher-order thinking skills where students analyzed, evaluated, and used their creativity in answering the problems given. The results of this study can inform the policy making for teachers in designing mathematics learning and for lecturers to carry out mentoring for teachers in designing mathematics learning based on Realistic Mathematics Education (RME) and ICT media.